Collaborative Strategy in Improving the Quality of Extracurricular Services in Elementary Schools - Rifa'i, Moh; Mubarok, Naufal (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
The aim of this research is to find out the cooperation strategy for improving the quality of extracurricular services at MI Mambaul Ulum Bondowoso. This research uses a qualitative-descriptive approach. School leaders, teachers, and parents are informants who participated in this study. Data collection methods involve in-depth interviews, observations of educational activities, and document analysis. Source triangulation and data triangulation techniques are used to ensure the validity of the data. Research findings reveal some findings. First, extracurriculars can support each other and create holistic education. Second, integrated extracurricular service quality implementation also involves coordinated teacher resources, being a benchmark in reaching students with diverse motivations, and contributing to future development policy formulation.